2010
DOI: 10.1590/s0103-84782010000100024
|View full text |Cite
|
Sign up to set email alerts
|

Consumo, digestibilidade de nutrientes e parâmetros sanguíneos de cabras mestiças moxotó suplementadas com óleos de licuri ou mamona

Abstract: Consumo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
1
4
0
7
Order By: Relevance
“…Regarding the ether extract apparent digestibility (EEAD), there was an increase when animals received a supplement with oils, probably due to the higher ether extract intake (EEI), similar to results found by Maia et al (2010), who also reported higher EEAD when animals were fed "licuri" or castor oil.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Regarding the ether extract apparent digestibility (EEAD), there was an increase when animals received a supplement with oils, probably due to the higher ether extract intake (EEI), similar to results found by Maia et al (2010), who also reported higher EEAD when animals were fed "licuri" or castor oil.…”
Section: Resultssupporting
confidence: 79%
“…In all diets analyzed, there was a good amount of fiber (500 g of hay/kg of DM) in the diet, which may have contributed to these results, once the fiber content possibly competed with the binding of fatty acids to the food particles in the rumen, thus preventing interference on ruminal fiber digestion (Bateman & Jenkins, 1998). Maia et al (2010) evaluated different contents (30 and 50 g/kg of DM) of "licuri" or castor oil in diets of lactating goats with 470 g of hay/kg of DM and did not observe changes in the apparent digestibility of DM. Similarly, Palmquist & Griinari (2006) did not find adverse effect on ruminal fermentation with the addition of a combination of sunflower and fish oils in cattle diets with 600 g of fiber/kg of DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fonseca and Soto-Blanco (2014), also highlight the toxic potential of this glycoprotein, mentioning its possible use as an agent of war or bioterrorism. It is important to note that the processed oil itself is not toxic since ricin, the toxic protein, is largely removed during the extraction process (Maia et al 2010). The inhabitants of the Franco rural community know the danger that the species represents, mainly for children and domestic animals.…”
Section: Ricinus Communis Lmentioning
confidence: 99%
“…A extração inicial é feita por preensagem mecânica, removendo apenas cerca de 45% do óleo presente nas sementes, e a obtenção do restante de óleo ocorre por meio de solventes como hexano, heptano, éteres de petróleo (OGUNNIYI, 2006). O óleo obtido não contém a toxina ricina, pois a proteína da semente permanece no subproduto da extração (MAIA et al, 2010).…”
Section: Produtos Da Mamonaunclassified